Repeated Supera stent fracture following stenting for popliteal artery occlusion: a case report - Byung Chan Lee; Chan Park; Hyoung Ook Kim; Ho Kyun Lee (Journal of International Medical Research)
The popliteal artery segment is particularly challenging for endovascular treatment. Stents used for treating popliteal artery lesions are usually associated with an increased risk of stent fracture and re-occlusion. The Supera stent is designed to withstand mechanical stress, with a low risk of fracture. A man in his mid-70s with left popliteal artery occlusion was treated with a Supera stent implantation. After 5 months, he revisited our hospital complaining of left leg pain. Preprocedural computed tomography angiography showed popliteal artery occlusion associated with a Supera stent fracture. A new Supera stent was implanted at the previous stent fracture site. However, 3 months after the second procedure, computed tomography angiography showed popliteal artery re-occlusion associated with a repeated fracture of the Supera stent. A femoral-popliteal bypass was performed. At the 6-month follow-up, computed tomography angiography showed a patent graft. Our findings indicated that recurrent fractures occurred after additional Supera stenting at the previous Supera stent fracture site. Careful observation is necessary after deploying a new Supera stent for treating a Supera stent fracture because of the possibility of a repeated fracture.